Effects of curzerene and Smyrnium cordifolium Boiss. extract on addiction withdrawal syndrome in mice - Pari Nazari; Parichehreh Yaghmaei; Alireza Rangin; Naser Abbasi (Shahrekord University of Medical Sciences, 2018)
Introduction: The purpose of this study was evaluating the effect of Smyrnium cordifolium extract (SCE) and curzerene (Cur) on withdrawal syndrome in mice compared with clonidine. Methods: High-performance liquid chromatography (HPLC) was used to determine the active ingredients of S. cordifolium. To evaluate the effects of SCE and Cur, 64 mice were divided into 8 equal groups. Groups 1, 2 and 3 were treated Cur (0.03, 0.06, 0.12 mg/kg, respectively). Groups 4, 5 and 6 were treated with SCE (100, 200, 300 mg/kg, respectively). The seventh group received just morphine. Group 8 received morphine and clonidine (0.2 mg/kg). Results: The results of this study showed that Cur was the most important ingredient in the extract of the plant, and the hydroalcoholic extract yield of S. cordifolium was 17.55% (w/w). The dose of 100 mg/kg of extract (SCE100) and 0.03 mg/kg curzerene (Cur1) (P < 0.05), dose of 200 mg/kg of extract (SCE200) and dose of 0.06 mg/kg curzerene (Cur2), (P < 0.01), dose of 300 mg/kg of extract (SCE300) and dose of 0.12 mg/kg of curzerene (Cur3) (P < 0.001) decreased the symptoms compared to clonidine. Doses higher than 300 mg/kg of extract and 0.12 mg/kg of Cur had fatal effects. All doses of SCE and Cur in comparison with the control group at significant level (P < 0.001) reduced the number of jumping, rearing and teeth chattering in morphine-dependent mice. Conclusion: The findings suggest that SCE and Cur are capable of reducing the symptoms of withdrawal syndrome and their effectiveness may be more than clonidine in reducing the addiction withdrawal syndrome, which may have human therapeutic potential.